Case Study Strategy in Science Education: A Systematic Review of Student Learning Outcomes - Ristiana, Evi (Universitas Khairun, 2025)
Mastery learning emphasizes full mastery of the material before students move on to the next stage. This approach includes formative evaluation, remedial for students who have not mastered the material, and enrichment for those who understand the material more quickly. This study uses the Systematic Literature Review (SLR) method to analyze the relationship between mastery learning and students' science learning outcomes based on 16 articles and 4 books. The results of the analysis show that mastery learning improves conceptual understanding, learning motivation, science learning outcomes, and student engagement. Strategies such as Student Teams Achievement Division (STAD), Mind Mapping, and Examples Non Examples have proven effective in improving learning mastery. However, challenges such as time constraints, teacher readiness, and differences in student learning speeds need to be addressed with additional guidance and periodic formative evaluation to optimize science learning outcomes